Flower strip farmscaping to promote natural enemies diversity and eco-friendly pest suppression in okra (Abelmoschus esculentus) - MEENA, ANIL; SHARMA, R K; CHANDER, S; Sharma, D K; SINHA, S R (The Indian Journal of Agricultural Sciences, 2019)
Investigations were conducted on flower strip farmscaping along with intercropping to promote natural enemy diversity and eco-friendly pest suppression in okra during kharif 2016 and 2017. Pooled data of both the years revealed that whitefly was lowest (7.66 /15 leaves) in biopesticides treated okra having baby-corn as an intercrop with flower plants strip. Likewise, a minimum population of leafhoppers (39.89/15 leaves), red spider mites (99.16/cm2/15 leaves) and lowest fruit infestation by fruit borer (9.60%) were observed on treated okra having cowpea as an intercrop with flower strip farmscaping. Maximum population of natural enemies, viz. coccinellids (5.40), spiders (6.38), Geocoris bug (2.47), rove beetles (1.99/5 plants) and carabid beetles (1.32/2 pitfall traps) were recorded on untreated okra with cowpea intercropping having flower strip farmscaping. Shannon-wiener index value was found lower for pests on okra treatments having flower strips, while index value was higher for natural enemies on same treatments.